Persistence of the reproductive toxicity of chlorpiryphos-ethyl in male Wistar rat - Augustave Kenfack; Ferdinand Ngoula; Paul Désiré Womeni Dzeufiet; Omer Bébé Ngouateu; Tsambou Megnimeza Astride Martine; Judith Kegne Chombong; Guylène Marie Zambou Zeukeng; Isabelle Leinyuy Nyuysemo; Arthenice Jemima Noumamo Guiekep; Tah Patience Nain; Pierre Kamtchouing; Joseph Tchoumbou; et al. (Asian Pacific Journal of Reproduction, 2015)
Objective: To study the effects of chlorpiryphos-ethyl (CE) on male fertility. Methods: Rats were gavaged daily from 30 to 120 days old with four doses of CE (10.50; 5.25; 3.50 and 0.00 mg/kg) and thereafter followed up for 90 additional days. Following this period of observation, each male rat was submitted to a fertility test with two virgin females. Male were then sacrificed and organs collected while females were followed up till delivery. Results: The weights of the testis and epididymis were lower (P<0.05) in rats treated with 10.50 mg/kg CE dose compared to controls. A decrease in the number of sperm per cauda epididymis was recorded in rat given the highest dose of CE with respect to the control value. The sperm motility was lower (P<0.05) in all CE-treated groups compared to the controls. Severe histological abnormalities were observed in testes of treated rats. The males exposed to the highest dose of CE did not produce any offspring. Conclusion: The effects of CE on reproductive system were persistent 90 days after the end of exposure.